2018
DOI: 10.1016/j.chest.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Can Patients With COPD Assimilate Disease-Specific Information During an Acute Exacerbation?

Abstract: ClinicalTrials.gov; No.: NCT02321215; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…It aims to achieve a proactive attitude towards their pathology, but its influence on clinical results has not been sufficiently investigated. This study has found that our educational program is similar in terms of educational results to programs carried out in other countries such as Canada or Sweden; 11 13 despite the fact that patients included in our study, had a recent diagnosis and had not received information previously about their disease. The domains of the questionnaire in which patients have the greatest IN are “Diet” and “Self-care”.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It aims to achieve a proactive attitude towards their pathology, but its influence on clinical results has not been sufficiently investigated. This study has found that our educational program is similar in terms of educational results to programs carried out in other countries such as Canada or Sweden; 11 13 despite the fact that patients included in our study, had a recent diagnosis and had not received information previously about their disease. The domains of the questionnaire in which patients have the greatest IN are “Diet” and “Self-care”.…”
Section: Discussionsupporting
confidence: 62%
“…It has been used to evaluate respiratory rehabilitation programs, 10 in other types of educational programs for patients with COPD in outpatient clinics 11 , 12 or during hospital admissions. 13 This questionnaire has been previously validated 9 and translated into several languages including Spanish. 14 However, the LINQ has never been used to assess which COPD Characteristics are correlated with information needs (IN), nor how IN influence moderate COPD exacerbations or admissions due to exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…The most used components in the interventions were aerobic training, strength training, breathing techniques and education and psychosocial support, either in isolation [19,25,27,30,32,41,45,47,48,52,54,55,58,59] or in combination [18, 20-24, 26, 28, 29, 31, 33-40, 42-44, 46, 49-51, 53, 56, 57], both of which are also common in pulmonary rehabilitation practice with patients with stable COPD [60]. Nevertheless, during AECOPD, patients present an increased airway and systemic inflammation that results in increased dyspnoea, cough and sputum volume and purulence, and further impairment of muscle strength, functionality and exercise tolerance and, hence, different characteristics and needs from those in the stable phase [1,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Quality assessment of the included studies with the Delphi List In total, 3569 patients with a mean age of 69.1 years and a mean FEV 1 of 39.4% predicted (data gathered from 35 studies, as seven of the included studies did not report the mean FEV 1 % pred) were enrolled in the included studies.Studies evaluated the effect of the applied intervention on patients' exercise capacity (n=23, ES range −1.8-5.0)[21,22,, muscle strength (n=11, ES −0.5-1.5)[26, 27, 36-38, 40-43, 45, 46], lung function (n=17, ES −3.0-1.4)[22, 24-26, 30, 32, 33, 37, 39, 40, 42, 46-51], functionality (n=7, ES −1.7-6.8) [31, 40, 41, 45, 46, 52, 53], physical activity levels (n=3, ES 1.2-2.6) [26, 41, 47], vital signs and peripheral oxygen saturation (n=10, ES −3.1-3.4) [24, 29, 31, 32, 36, 37, 39, 42, 48, 50], symptoms (n=26, ES −4.0-4.8) [20-25, 28, 29, 31-34, 36, 37, 42, 45-55], impact of disease (n=4, ES −5.1-0.9) [30, 31, 44, 49], disease severity (n=3, ES −4.7-−0.3) [22, 29, 31], HRQoL (n=25, ES −3.0-6.1) [18, 20-24, 26, 28-31, 33, 35, 36, 38, 39, 42, 46-48, 51, 55-58], length of stay (n=19, ES −0.8-0.9)[20, 22, 25, 26, 30, 36, 37, 40-43, 45, 46, 48, 49, 51-53, 56], new exacerbations (n=4, ES 0.1-1.0)[23,33,36,38], hospital readmissions (n=14, ES 0.1-1.8)[19,21,22,29,33,35,38,43,44,47,52,[56][57][58], and mortality (n=10, ES 0.1-1.2)[18,19,21,22,37,44,54,[56][57][58]. Additionally, studies also assessed patients' knowledge (n=4, ES −0.3-15.1)[21,47,56,59], satisfaction (n=4, ES 0.2-9.3)[47,…”
mentioning
confidence: 99%
“…Although the authors of this study concluded that the intervention was feasible, only 30% of the approached patients accepted participation, and retention at 2 weeks was only 52%. In a recent pilot randomized, controlled trial (27), where a brief education program (with no exercise…”
Section: Discussionmentioning
confidence: 99%